Кажани триби Myotini (Mammalia) у Середньому Подніпров’ї: видовий склад, поширення та чисельність - Загороднюк, І.В.; Годлевська, О.В. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
Триба представлена в Приднепровье 4 видами. Оригинальные и литературные данные, коллекционные образцы подтверждают присутствие здесь двух видов Leuconoe: L. dasycneme и L. daubentonii. Два других вида, представляющие род Myotis (M. «mystacinus» и М. nattereri), известны по единичным находкам. Предположения о распространении еще двух видов рода Myotis (М. myotis, M. bechsteinii) являются ошибочными. Оба Leuconoe известны по находкам и в летнее, и в осенне-зимнее время, на основании чего рассматриваются как оседлые. Зимние находки ночниц происходят преимущественно из искусственных подземелий высокого правого берега Днепра. Общее число регистрации видов (в ряду L. daubentonii, L. dasycneme, M. nattereri, M. «mystacinus») соотносится как 66 : 14 : 6 : 4, а число их особей — как 667 : 61 : 29 : 5 соответственно. The tribe is represented in the region by four species. Original data and collected samples as well as published data verify presence of two Leuconoe species, namely L. dasycneme, and L. daubentonii. Two other species represented genus Myotis (M. «mystacinus» and M. nattereri) are recorded by single records each. Assumptions on the occurrence of two more species of Myotis (M. myotis and M. bechsteinii) are erroneous. Both Leuconoe species are known to occur in both winter and autumn-summer time, and they are considered sedentary species. Winter records of Myotini originate mainly from artificial caves of the steep right bank of Dnipro River. Total numbers of species records (L. daubentonii, L. dasycneme, M. nattereri, M. «mystacinus») form a ratio 66 : 14 : 6 : 4, and numbers of their specimens are 667 : 61 : 29 : 5 respectively.